-56=-c-(-8)

Simple and best practice solution for -56=-c-(-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -56=-c-(-8) equation:


Simplifying
-56 = -1c + -1(-8)

Multiply -1 * -8
-56 = -1c + 8

Reorder the terms:
-56 = 8 + -1c

Solving
-56 = 8 + -1c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add 'c' to each side of the equation.
-56 + c = 8 + -1c + c

Combine like terms: -1c + c = 0
-56 + c = 8 + 0
-56 + c = 8

Add '56' to each side of the equation.
-56 + 56 + c = 8 + 56

Combine like terms: -56 + 56 = 0
0 + c = 8 + 56
c = 8 + 56

Combine like terms: 8 + 56 = 64
c = 64

Simplifying
c = 64

See similar equations:

| 4x+5=6.5 | | 3n^2+9n-12=0 | | 2(x+2)-5(2x+7)= | | 7x+2=-103 | | 2x+10-3=-2x+1 | | 10-2*x=4 | | -.75+j=-3.5 | | 4x+126=11x | | 19-2*x=4 | | 96=-24c | | -6a-5b-4= | | -3.75+j=-3.5 | | 96=-24 | | 4-3*x=34 | | 2x+7y+8= | | (v-3)(2v+1)= | | 6a-5b-4= | | 2-6*x=5 | | z^3-3z^2+(1+3i)z-6i+a=0 | | 2a^2-ab-15b^2=0 | | .5*x+1=11 | | c=15+40 | | 4x+10=x+37 | | -4+2t=1 | | 58=3a+10 | | 5-2*x=19 | | 8y+23=33 | | 3x+1=-7-5x | | 533.71=40y+2.5y | | y=40y+2.5y | | 2y-2x+6=0 | | 9-1=t+(-19) |

Equations solver categories